About according to the concept of a corruption offense crimes provided for by Article 45 of the Criminal Code of Ukraine - Ярмиш, Наталія Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In Article 45 of the Criminal Code of Ukraine contains a list of offenses which are belongs to corruption. The assignment of a crime to corrupt entails limiting the culprit in many positive opportunities (in particular, the exemption from probation). In fact, not all crimes from the list meets the corruption offense, as defined in the Law of Ukraine "On Prevention of Corruption". Corruption offenses related to at least the purpose of obtaining or giving undue advantage to certain subject. However, such a goal is not mandatory for offenses under Part. 2 art. 320 of the Criminal Code, which establishes liability for violation of the rules of narcotic drugs and art. 357 of the Criminal Code, which refers to the various ways of taking possession of documents, stamps, seals as well as the destruction of these items. But both articles contained in the list of corruption crimes. On the other hand, crimes under Art. Art. 365, 370 of the Criminal Code "Abuse of power by a law enforcement authority" and "Provocation of bribery." were not included in the list of corruption crimes. However, in the case of appropriate action in order to obtain undue advantage of such crimes can be attributed to corruption. Among the subjects of corruption in the Law of Ukraine "On Prevention of Corruption" not specified "physical" (private) entity. In spite of this crime is committed by such entities, the list of corruption contains. According to the same law, corruption in the form of offers, promises, and giving of an undue benefit associated with the authorized person to persuade it to illegal actions, and in the list of crimes of corruption are no updates. Thus the note of art. 45 of the Criminal Code should be recognized so that part does not conform to the Law of Ukraine "On Prevention of Corruption".